Sathānakān dek nai phāwa yāklambāk Čhangwat Chīang Mai (Khrōngkān Phūying Thai nai Wan Phrungnī, Khana Sangkhommasāt, Mahāwitthayālai Chīang Mai, 2000)
On socioeconomic status of children and child labor problems in Chiang Mai Province, Thailand.